PELATIHAN APLIKASI JASA KURIR ONLINE PADA PEGAWAI MINI MARKET BORNEO MART BANJARBARU - Mokhamad Ramdhani Raharjo; Ihda Innar Ridho; Fauzi Yusa Rahman (Universitas Islam kalimantan MAB, 2018)
Application training of shipping services in orderly ordering using online application is something that must be known by business actors, especially mini business actors to improve the results of the business. The target of this training activity is the employee or employee of mini market borneo mart banjarbaru. With this training, employees are expected to understand and can operate the application of online courier services to products sold from goods ordered by the buyer. Benefits of dedication activities to be achieved is the target audience can operate the application well so that it becomes one of the efforts to improve employee performance of mini market borneo mart so that good impact to buyer or consumer in terms of satisfaction to service. From the result of the training, it can be concluded that the trainees saw the practice and some question and answer about the application that was held 88% of the participants can operate the material given.